Optimalisasi Kegiatan Online dan Offline dalam Kampanye Pencegahan COVID-19 - Yuliarti, Monika Sri (Universitas Nusantara PGRI Kediri, 2021)
The COVID-19 pandemic has an effect on all countries, including Indonesia. Universitas Sebelas Maret (UNS) Surakarta sees this phenomenon as a condition that should be able to become a forum for students to take part in prevention efforts, through the Community Service Program for COVID-19. Eight students from the department of Communication Science of UNS are members of the COVID-19 KKN group under the guidance of a lecturer to apply knowledge and skills from the campus to the community in the environment where they live. With data on COVID-19 cases that are still increasing, the KKN COVID-19 team plays an important role in their respective neighborhoods (Jakarta, Surakarta, Sukoharjo, and Wonogiri areas). Apart from data on positive cases of COVID-19 which is still high, the background for this activity is that the people in the target areas are still not optimally running the new normal protocol. The KKN COVID activities are carried out both offline and online, with the majority of activities online considering physical distancing. From this activity, public awareness can increase, and knowledge and information related to COVID-19 will also increase.